VALUING RECYCLED WASTE PAPER BY THE DESIGN AND MANAGEMENT OF A BOOK COVER MODEL-YRR.18 - Jenny Ria Rajagukguk (Universitas Airlangga, 2020)
ABSTRACTNatural materials are increasingly limited, encouraging the use of materials such as waste materials that have not been widely used for building materials or manufacturing products. Waste paper has been used as a material for the book-YRR.18 book cover through management and design approaches. The waste paper materials used are better than those used to produce this book cover: cellulose = 45.80% = pentosan 25.90% and lignin = 22.60%. Therefore, this research aims to provide product design from environmentally friendly materials and analysis of the value of its products in terms of loss-profit, so that it can be a profitable business potential for book producers in Indonesia as well as encourage book producers in Indonesia to being involved in efforts to save the environment.Keywords: Waste Paper Material; Product Value; Design Book Cover Model-YRR. 18. ABSTRAKBahan-bahan alami yang semakin terbatas, mendorong penggunaan bahan-bahan seperti bahan limbah yang belum banyak dimanfaatkan untuk bahan bangunan atau pembuatan produk. Kertas bekas selama ini digunakan sebagai bahan pembuatan sampul buku Model -YRR.18 melalui pendekatan manajemen dan desain. Bahan limbah kertas yang digunakan lebih baik daripada yang digunakan untuk memproduksi sampul buku ini adalah: selulosa = 45,80% = pentosan 25,90% dan lignin = 22,60%. Oleh karena itu, penelitian ini bertujuan untuk memberikan desain produk dari bahan ramah lingkungan dan analisa nilai produknya dari sisi loss-profit, sehingga dapat menjadi potensi bisnis yang menguntungkan bagi produsen buku di Indonesia sekaligus terlibat dalam upaya penyelamatan lingkungan.Kata kunci: Bahan Limbah Kertas; Nilai Produk; Desain Sampul Buku Model-YRR.18.